A strong charge-transfer effect in surface-enhanced Raman scattering induced by valence electrons of actinide elements1. Issue 41 (7th May 2015) - Gao, Yang; Chen, Lei; Dai, Xing; Song, Ruixia; Wang, Bo; Wang, Zhigang
<x xml:space="preserve">Abstract</x> The 6d electrons of Ac atom involved in excited transitions induce a strong CT-SERS enhancement which can be tuned by changing the conformation of pyridine-Ac@Au7 complexes.